GAMBARAN KEHAMILAN EKTOPIK TERGANGGU DI RSUP PROF. DR. R. D. KANDOU MANADO PERIODE 1 JANUARI 2012 - 31 DESEMBER 2013 - Lomboan, Pricilia S.; Mamengko, Linda; Wantania, John (Universitas Sam Ratulangi, 2015)
Abstract: In ectopic pregnancy, fertilized ovum is implanted and grows not in a normal place in the endometrium of the uterine cavity. If such pregnancy is threatened to an abortion then it is called threatened ectopic pregnancy. This study aimed to obtain the description of ectopic pregnancy at Prof. Dr. R. D. Kandou Hospital Manado related to age, husband’s job, marriage status, parity, pregnancy age, history of abortion, history of fluor albus, implantation site, and hemoglobin level. This was a retrospective descriptive study. The population consisted of all patients treated at Department of Obstetrics Gynecology Prof. Dr. R. D. Kandou Manado Hospital from January 1, 2012 - December 31, 2013. The results showed that of the 49 cases of ectopic pregnancy most of the patients were at the age of 21-35 year (65.30%); their husbands did not have any jobs (77.55%); married (73.46%); parity of 2 (32.65%); pregnancy age <8 weeks (55.10%); had no history of abortion (65.30%) or of fluor albus (81.63%); location in ampullae of uterine tube (97.95%); Hb level 9-10 g% and >10 g% (32.65%).Keywords: ectopic pregnancy, threatened ectopic pregnancyAbstrak: Kehamilan ektopik adalah kehamilan dengan ovum yang dibuahi berimplantasi dan tumbuh tidak di tempat yang normal yakni endometrium kavum uteri. Bila kehamilan tersebut mengalami proses pengakhiran (abortus) maka disebut kehamilan ektopik terganggu (KET). Penelitian ini bertujuan untuk mengetahui gambaran kehamilan ektopik terganggu di RSUP Prof. Dr. R. D. Kandou Manado dari segi umur, pekerjaan suami, status perkawinan, paritas, usia kehamilan, riwayat abortus, riwayat keputihan, lokasi implantasi, dan kadar Hb. Penelitian ini mnggunakan metode deskriptif retrospektif. Populasi ialah seluruh pasien yang dirawat di Bagian Obstetri Ginekologi RSUP Prof. Dr. R. D. Kandou Manado periode 1 Januari 2012 – 31 Desember 2013. Hasil penelitian memperlihatkan dari 49 kasus KET, pasien terbanyak berumur 21-35 tahun (65,30%); suami yang tidak bekerja (77,55%), status menikah (73,46%), paritas 2 (32,65%), usia kehamilan <8 minggu (55,10%), tanpa riwayat abortus (65,30%), tanpa riwayat keputihan (81,63%), lokasi pada ampula tuba (97,95%), serta kadar Hb 9-10 g% dan Hb >10 g% (32,65%).Kata kunci: kehamilan ektopik, KET